Phytochemical and Bioactivity Studies on Hedera helix L. (Ivy) Flower Pollen and Ivy Bee Pollen - Nisa Beril Sen; Etil Guzelmeric; Irena Vovk; Vesna Glavnik; Hasan Kırmızıbekmez; Erdem Yesilada (MDPI AG, 2023)
Bee pollen, known as a 'life-giving dust', is a product of honeybees using flower pollen grains and combining them with their saliva secretions. Thus, flower pollen could be an indicator of the bee pollen botanical source. Identification of bee pollen sources is a highly crucial process for the evaluation of its health benefits, as chemical composition is directly related to its pharmacological activity. In this study, the chemical profiles, contents of phenolic marker compounds and pharmacological activities of Hedera helix L. (ivy) bee pollen samples from Türkiye and Slovenia, as well as ivy flower pollen grains, were compared. High-performance thin-layer chromatography (HPTLC) analyses revealed that pollen samples, regardless of where they were collected, have similar chemical profiles due to the fact that they have the same botanical origins. Marker compounds afzelin, platanoside and quercetin-3-O-β-glucopyranosyl-(1→2)-β-galactopyranoside, common to both bee pollen and flower pollen, were isolated from bee pollen, and their structures were elucidated by nuclear magnetic resonance (NMR) and mass spectrometry (MS). These three compounds, as well as chlorogenic acid and 3,5-dicaffeoylquinic acid (found in flower pollen), were quantified using high-performance liquid chromatography (HPLC) analyses. In vitro tests and effect-directed analyses were used to evaluate the xanthine oxidase inhibition and antioxidant activity of the marker compounds and extracts from flower pollen and bee pollen. This is the first report comparing chemical profiles and related bioactivities of the flower pollen and bee pollen of the same botanical origin, as well as the first report of the chemical profile and related bioactivities of ivy flower pollen.